Effect of Problem-Based Learning (PBL) on Science Learning Outcomes - Susanti, Heni (Social, Humanities, and Educational Studies (SHES): Conference Series, 2021)
In general, learning in elementary schools does not use innovative learning models so that students are less creative. Science learning emphasizes student involvement in the active learning process and trains students to think critically and objectively. The Problem Based Learning (PBL) learning model is a learning strategy that provides opportunities for students to think more critically, actively and learn independently so that student learning outcomes will increase. Learning by applying the Problem Based Learning model has had an influence with an effect size price of 0.75% on science learning outcomes in grade IV SDN 12 Pontianak Selatan. There is a significant difference in science learning outcomes between groups of students who are taught using the PBL learning model and groups of students who are taught with conventional learning, this shows that the application of the PBL learning model affects the science learning outcomes of grade V elementary school students.